2012
DOI: 10.1093/bja/aer448
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral haemodynamic physiology during steep Trendelenburg position and CO2 pneumoperitoneum

Abstract: Prolonged steep Trendelenburg positioning and CO(2) pneumoperitoneum does not compromise cerebral perfusion. ZFP and eCPP are reliable variables for assessing brain perfusion during prolonged steep Trendelenburg positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Measurement of cerebral blood flow can be assessed by transcranial Doppler measurements of both anterior and posterior cerebral circulation. The benefit of transcranial Doppler in this regard has been proven (11,12). The present study was designed by accepting the cerebral blood flow of the patients as normal and considering that both anterior and posterior blood supply of the brain was natural.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of cerebral blood flow can be assessed by transcranial Doppler measurements of both anterior and posterior cerebral circulation. The benefit of transcranial Doppler in this regard has been proven (11,12). The present study was designed by accepting the cerebral blood flow of the patients as normal and considering that both anterior and posterior blood supply of the brain was natural.…”
Section: Discussionmentioning
confidence: 99%
“…Jugular venous oxygen saturation does not seem to reflect brain oxygenation better than rSO 2 in this condition [42]. This condition was also not found to compromise cerebral perfusion [43,44]. Most importantly, all of these non-physiological conditions were still within normal limits, and therefore well tolerated by most patients [34,44].…”
Section: Prostatectomymentioning
confidence: 75%
“…Also combining pneumoperitoneum with Trendelenburg increases the ICP further and this may hinder cerebral oxygenation [26] . Kalmar et al [27] examined patients undergoing RALRP which were exposed to prolonged steep Trendelenburg position and CO 2 pneumoperitoneum and suggested that it does not compromise cerebral perfusion. Though, it is advised to keep the patient in normocapnic range because regional cerebral oxygen saturation (rSO 2 ) is correlated with the increase in partial pressure of CO 2 (PaCO 2 ).…”
Section: Effects On Neurological Systemmentioning
confidence: 99%